HUBUNGAN TINGKAT PENGETAHUAN PERILAKU HIDUP BERSIH DAN SEHAT DENGAN PERILAKU KEBERSIHAN PRIBADI PADA SISWA SD YPPK SANTO YUSUF SORPEHA FAK-FAK PAPUA BARAT - Penaonde, Lidia Evling Monika; Toar, Jilly; Bawiling, Nancy S. (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Clean and healthy living behavior (PHBS) in the school environment is an effort of students and teachers on the basis of awareness to prevent disease, create a healthy environment that is free from disease, and efforts to improve the quality of health for themselves. School is one of the best educational places to teach the importance of knowledge to implement clean and healthy living behavior. The purpose of this study is the relationship between clean and healthy living behavior and the level of knowledge of personal hygiene in students of SD YPPK Santo Yusuf Sorpeha. This research design uses descriptive correlation with a cross sectional approach. The sample used in this study was 33 people. Data collection techniques using questionnaires. There is a significant relationship between the level of knowledge of clean and healthy living behavior with personal hygiene behavior in elementary school students of Yppk Santo Yusuf Sorpeha Fak-Fak West Papua. (r = 0.382 and p = 0.028).